Women as Teachers and Disciples in Early Buddhist Communities: The Evidence of Epigraphy - Collett, Alice (Religions of South Asia, 2015)
Inscriptions from ancient India reveal to us two related phenomena about early Buddhist nuns: firstly, that nuns were teachers of other women, and secondly that nuns considered themselves to be (or were recorded to be) direct disciples of male monastic teachers. The first of these is confirmed by the textual evidence, and sits as part of our picture of the lives of nuns at the time of the historical Buddha and subsequently. The second, however, challenges assumptions about the operations of early Buddhist communities. Monastic male-female teaching relationships, according to the textual evidence, were largely formal and institutional, as typified by the role of monk advisor to nuns (bhikkhunovadaka). As recorded in the texts, nuns should formally request instruction from monks, and certain monks were charged with dispensing such duties. The monastic male female teaching relationships recorded in the epigraphy do not chime with this state of affairs, instead suggesting that closer and more personal relationships existed.